Effect of Drilling Technique on the Early Integration of Plateau Root Form Endosteal Implants: An Experimental Study in Dogs - Giro, Gabriela [UNESP]; Marin, Charles; Granato, Rodrigo; Bonfante, Estevam A.; Suzuki, Marcelo; Janal, Malvin N.; Coelho, Paulo G. (W B Saunders Co-elsevier Inc, 2011)
Purpose: This study tested the hypothesis that early integration of plateau root form endosseous implants is significantly affected by surgical drilling technique.Materials and Methods: Sixty-four implants were bilaterally placed in the diaphysial radius of 8 beagles and remained 2 and 4 weeks in vivo. Half the implants had an alumina-blasted/acid-etched surface and the other half a surface coated with calcium phosphate. Half the implants with the 2 surface types were drilled at 50 rpm without saline irrigation and the other half were drilled at 900 rpm under abundant irrigation. After euthanasia, the implants in bone were nondecalcified and referred for histologic analysis. Bone-to-implant contact, bone area fraction occupancy, and the distance from the tip of the plateau to pristine cortical bone were measured. Statistical analyses were performed by analysis of variance at a 95% level of significance considering implant surface, time in vivo, and drilling speed as independent variables and bone-to-implant contact, bone area fraction occupancy, and distance from the tip of the plateau to pristine cortical bone as dependent variables.Results: The results showed that both techniques led to implant integration and intimate contact between bone and the 2 implant surfaces. A significant increase in bone-to-implant contact and bone area fraction occupancy was observed as time elapsed at 2 and 4 weeks and for the calcium phosphate-coated implant surface compared with the alumina-blasted/acid-etched surface.Conclusions: Because the surgical drilling technique did not affect the early integration of plateau root form implants, the hypothesis was refuted. (C) 2011 American Association of Oral and Maxillofacial Surgeons J Oral Maxillofac Surg 69: 2158-2163, 2011